Freedom of Expression in Regulatory Pressure: Case Study on the Electronic Information and Transaction Law - Indriasari, Devi Tri; Karman, Karman (Jurnal The Messenger, 2023)
Introduction: This article examined how internet regulations in Indonesia, specifically the Electronic Information and Transactions (EIT) Law, impacted freedom of expression in the digital space from 2008 to 2021. Methods: Qualitative research was conducted, employing a case study approach, utilizing literature studies and analyzing articles related to the EIT Law and freedom of expression violations. Findings: The study identified 371 instances where the EIT Law was used to prosecute individuals, often those exposing criminal activity online, highlighting a concerning trend of criminalizing victims. Articles 27, 28, and 29 were particularly problematic due to their ambiguity, creating opportunities to suppress online discourse. This analysis revealed a concerning pattern of the EIT Law being used to restrict digital freedom of expression and public participation, aligning with Althusser's (1970) concept of a repressive state apparatus. The research identified the government, entrepreneurs, and the police as the primary actors utilizing the EIT Law, often to the detriment of civil society members, reflecting the concept of hegemony. This study recommends further research into the EIT Law's impact on digital freedom of expression, focusing on the legislative process, the experiences of those affected by the law, and comparative analyses with other countries. Investigating the evolving landscape of digital rights about state control and corporate. Originality: This manuscript addressed a significant gap in existing literature by providing an in-depth analysis of the practical implications of Indonesia's Information and Electronic Transactions (ITE) Law on digital freedom of expression.